Involvement of central alpha(1)-adrenoceptors on renal responses to central moxonidine and alpha-methylnoradrenaline - Andrade, Carina A. F. de [UNESP]; Andrade, Glaucia M. F. de [UNESP]; De Paula, Patricia M. [UNESP]; De Luca, Laurival A. [UNESP]; Menani, José Vanderlei [UNESP] (Elsevier B.V., 2009)
Moxonidine (alpha(2)-adrenoceptor/imidazoline receptor agonist) injected into the lateral ventricle induces diuresis, natriuresis and renal vasodilation. Moxonidine-induced diuresis and natriuresis depend on central imidazoline receptors, while central alpha(1)-adrenoceptors are involved in renal vasodilation. However, the involvement of central alpha(1)-adrenoceptors on diuresis and natriuresis to central moxonidine was not investigated yet. In the present study, the effects of moxonidine, alpha-methylnoradrenaline (alpha(2)-adrenoceptor agonist) or phenylephrine (alpha(1)-adrenoceptor agonist) alone or combined with previous injections of prazosin (alpha(1)-adrenoceptor antagonist), yohimbine or RX 821002 (alpha(2)-adrenoceptor antagonists) intracerebroventricularly (i.c.v.) on urinary sodium, potassium and volume were investigated. Male Holtzman rats (n = 5-18/group) with stainless steel cannula implanted into the lateral ventricle and submitted to gastric water load (10% of body weight) were used. Injections of moxonidine (20 nmol) or alpha-methylnoradrenaline (80 nmol) i.c.v. induced natriuresis (196 +/- 25 and 171 +/- 30, respectively, vs. vehicle: 101 +/- 9 mu Eq/2 h) and diuresis (9.0 +/- 0.4 and 12.3 +/- 1.6, respectively, vs. vehicle: 5.2 +/- 0.5 ml/2 h). Pre-treatment with prazosin (320 nmol) i.c.v. abolished the natriuresis (23 +/- 4 and 76 +/- 11 mu Eq/2 h, respectively) and diuresis (5 +/- 1 and 7.6 +/- 0.8 ml/2 h, respectively) produced by i.c.v. moxonidine or alpha-methylnoradrenaline. RX 821002 (320 nmol) i.c.v. abolished the natriuretic effect of alpha-methylnoradrenaline, however, yohimbine (320 nmol) did not change renal responses to moxonidine. Phenylephrine (80 nmol) i.c.v. induced natriuresis and kaliuresis that were blocked by prazosin. Therefore, the present data suggest that moxonidine and alpha-methylnoradrenaline acting on central imidazoline receptors and alpha(2)-adrenoceptors, respectively, activate central alpha(1)-adrenergic mechanisms to increase renal excretion. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Sodium excretion; Urinary excretion; Adrenoceptor; Renal excretion; Prazosin